The protective role of interleukin‐18 binding protein in a murine model of cardiac ischemia/reperfusion injury. (5th October 2015) - Gu, Haifeng; Xie, Minghua; Xu, Liqian; Zheng, Xiaojun; Yang, Yunmei; Lv, Xueying
Summary: IL‐18, a proinflammatory cytokine, is produced by macrophages, epithelial cells, T cells, neutrophils, NK‐T cells, and B cells, and has been implicated in the pathophysiology of a variety of inflammatory diseases including ischemia/reperfusion (IR) injury, transplant rejection, and autoimmune disease. Recent study indicated that neutralization of IL‐18 with anti‐IL‐18 antibody or IL‐18‐binding protein (IL‐18BP) ameliorates IR‐induced myocardial injury. However, the mechanism needs to be further investigated. In our current study, syngeneic heterotopic heart transplantation was performed by a modified non‐suture cuff technique. We found that IL‐18BP treatment ameliorated cardiomyocyte necrosis and infiltration of CD4 + T cells, neutrophils, and macrophages. IL‐18BP‐treated mice exhibited decreased expression of inflammatory cytokines including IL‐1β, IL‐23, IL‐18, and IL‐17. IL‐18BP treatment suppressed Th17 differentiation in vivo and in vitro . Adoptive transfer of T cells from IL‐18BP‐treated mice showed alleviated cardiac IR injury when compared with that transferred from control mice. Furthermore, the decreased infiltration of mononuclear cells and production of troponin T (TnT) induced by IL‐18BP treatment were both abrogated by additional administration of recombinant mouse IL‐17 (rmIL‐17). These data revealed a protective role of IL‐18BP in cardiac IR injury. Above all, IL‐18BP ameliorates cardiac IR injury in part through suppression of Th17 differentiation.